2019
DOI: 10.29166/ciencias_medicas.v44i1.1970
|View full text |Cite
|
Sign up to set email alerts
|

Índices neutrófilo/linfocitos y plaquetas/linfocitos como predictores de mortalidad en sepsis.

Abstract: Introducción: Aunque existen diversos métodos para evaluar la severidad y la mortalidad de la sepsis basados en escalas y biomarcadores, no todos están disponibles en las instituciones de salud por su costo. Objetivo: Determinar si los índices de neutrófilos/linfocitos y plaquetas/linfocitos son adecuados predictores de gravedad y mortalidad en pacientes con sepsis y choque séptico Métodos: Estudio observacional analítico en 149 pacientes con sepsis y choque séptico en el Hospital Docente de Calder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Other cytometric indicators such as the absolute number of neutrophils and lymphocytes and their neutrophil/lymphocyte ratio, the latter promising under the physiopathological reasoning that in bacterial sepsis the neutrophil count increases and the lymphocyte count decreases, therefore the value of the same increases the greater the severity of the picture, were not useful in predicting mortality, this contrasts with some studies [29][30][31] and coincides with the results of a previous study by the same authors 32 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Other cytometric indicators such as the absolute number of neutrophils and lymphocytes and their neutrophil/lymphocyte ratio, the latter promising under the physiopathological reasoning that in bacterial sepsis the neutrophil count increases and the lymphocyte count decreases, therefore the value of the same increases the greater the severity of the picture, were not useful in predicting mortality, this contrasts with some studies [29][30][31] and coincides with the results of a previous study by the same authors 32 .…”
Section: Discussionsupporting
confidence: 65%
“…The cut-off points were determined on the ROC curve using the Youden index; for the EDW at baseline and at 48 hours the cut-off point was ≥14,50%, where the sensitivity was 62.50% at baseline and 69.57% at 48 hours, specificity 61.34% at baseline and 58.93% at 48 hours, PPV 32 The multivariate logistic regression model was used to determine the relationships with mortality using the cut-off points of the blood cytometry parameters. The results obtained showed that the initial EDW with p-value 0.005 and the initial MPV with p-value 0.004 are predictors of mortality, where for initial EDW ≥14,5, the probability of not surviving was increased by 5.25 times, while for MPV ≥8,45 fL the probability of not surviving was increased by 5,28 times.…”
Section: Resultsmentioning
confidence: 99%